Efektivitas Teknik Modeling Melalui Konseling Kelompok Untuk Meningkatkan Karakter Rasa Hormat Peserta Didik (Quasi Eksperimen Terhadap Siswa Kelas X di SMK Muhammadiyah 2 Bandung Tahun Pelajaran 2014/2015) (Jurnal Bimbingan dan Konseling Islam, 2015)
This research based on phenomenon of declining respect to the students behavior, especially at the school environment. Last few years the culture of courtesy in Indonesia has decreased from the younger generation or teenagers who tend to lose ethics and politeness towards peers, elders, teachers and even to parents. This study aimed to describe the effectiveness of modeling techniques to develop students character about respect. This research used a a quantitative approach with quasi-experimental  methods equivalent pretest-posttest control group design. Experimental group and control group was not chosen at random system. Symbolic modeling techniques was given to experimental group and conventional treatment for the control group, and last gave posttest to the  student. Data was collected by respect questionnaires. Study participants were 14 students and divided into experimental group (7 people) and control group (7 people). The results showed that group counseling services through modeling techniques effective to develop students character about respect.